2023
DOI: 10.1111/os.13668
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Revision for Long‐Term Symptomatic Cage Retropulsion after TLIF: The Clinical Presentation in a Single Center

Abstract: Background Cage retropulsion after transforaminal lumbar interbody fusion (TLIF) is a common complication that is more frequently detected in the early postoperative period. Revision in the early stages is relatively less difficult in symptomatic cases. However, cage retropulsion is quite rare for patients with intervertebral osseous fusion in the long term after TLIF, and there are no relevant reports related to the revision plan. Case presentation Here, we report a case of a patient who underwent L4‐S1 TLIF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Telfeian et al reported eight cases of posterior displacement of cage compressing the spinal canal and were endoscopically revised with transforaminal approach 4 . Xu et al described endoscopic revision technique for cage retropulsion after transforaminal lumbar interbody fusion 5 . However, lateral displacement of cage after OLIF was more rarely seen and would also cause neuromuscular symptoms 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telfeian et al reported eight cases of posterior displacement of cage compressing the spinal canal and were endoscopically revised with transforaminal approach 4 . Xu et al described endoscopic revision technique for cage retropulsion after transforaminal lumbar interbody fusion 5 . However, lateral displacement of cage after OLIF was more rarely seen and would also cause neuromuscular symptoms 2 .…”
Section: Introductionmentioning
confidence: 99%
“… 4 Xu et al described endoscopic revision technique for cage retropulsion after transforaminal lumbar interbody fusion. 5 However, lateral displacement of cage after OLIF was more rarely seen and would also cause neuromuscular symptoms. 2 A few papers have reported that open surgery through the posterior approach was used to manage this complication.…”
Section: Introductionmentioning
confidence: 99%